Co-teaching strategy as support to improve classroom management and student performance of 1st, 2nd and 3rd years of baccalaureate levels in the teaching-learning process of the english language at Simón Bolívar high school in Puerto Bolívar-Machala, during the academic year 2013- 2014. - Señalin Aguirre, Priscila Vanessa (Machala : Universidad Técnica de Machala, 2015)
The implementation of new models for successful teaching of a second language has been an anticipated event in Ecuador. Likewise, it is well known that changing the way of teaching requires not only a commitment among authorities and teachers but also taking account of student needs and viewpoints. In fact, it is essential a detailed research to the establishment of Co-Teaching as a strategic model, for that reason the current paper is divided in sections, as follows: Chapter I discusses why there is low academic performance regarding English language in Baccalaureate students at Simón Bolívar High School, and identifies the current effects and possible causes of the issue. In addition, objectives are defined and it is highlighted the importance of the implementation of a Co-Teaching model in order to improve the class management and certainly, increase the quality of teaching. Chapter II stresses the key definitions for the right development and understanding of the paper. Here is also the historical background of the thesis. Chapter III outlines the methodology to be used variables, indicators and hypothesis are formulated. On top of that it is recognized the universe and sample size of people involved in the issue of this paper. Chapter IV addresses presentation of scientific research results. That is display of graphs and charts, analysis, interpretation, verification of hypothesis and the respective conclusions and recommendations. Chapter V deals with the proposal, description, resources required, chronogram and a discussion which explains in advance what will occur in the presentation to the authorities and English teachers.
Keywords: CO-TEACHING; MANAGEMENT; BACCALAUREATE; STRATEGY